Optimalisasi Pemesanan Sarana Olahraga Bulutangkis di GOR Lodaya Kota Bandung - Muhammad Anandi Noerrachman; Ilham Gemiharto; Meria Octavianti (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
This study aims to find out how the communication strategy is carried out in the process of ordering badminton sports facilities at the Lodaya Sports Hall in Bandung City with an Exploratory Case Study Approach. The aspects studied included knowing how the communication strategy was carried out, why the communication strategy was used, knowing how the evaluation was carried out, and knowing why optimization needed to be done in the process of ordering badminton sports facilities at Lodaya Sports Hall, Bandung City. This study used a qualitative research approach with an exploratory case study research method. Data collection was carried out through in-depth interviews and observation. Then a technical triangulation technique was carried out to test the validity of the research data. The results of the study show that the Lodaya Sports Hall in Bandung City applies an offline communication strategy to the process of ordering badminton sports facilities. This strategy was carried out because the managers of the Lodaya Sports Hall in Bandung City felt they could trust customers who came directly to the field and there were limited resources on the part of the manager. The evaluation was carried out by the manager of GOR Lodaya Bandung City with the results of the evaluation showing that there was a negative effect received by the customer. Customers feel that there are limitations to accessibility and efficiency of the ordering schedule, as well as that there is an uneven implementation of the transparency of the ordering system which results in difficulty ordering badminton sports facilities. Optimization is needed to fulfill the objectives of GOR Lodaya Bandung City, which is to provide badminton sports facilities for all levels of society.